Technology of Growing Appliants in a New Form in the Motherland (Eurasian Scientific Herald, 2022)
The article describes the technology of growing new varieties of apple seedlings in the native nursery. The results of the new type’s bugs of apples for apples inoculation in the conditions of head and nursery for vegetative reproducing are given in this article.